A COMPARISON OF CAUSALITY ASSESSMENT TOOLS FOR SUSPECTED ADVERSE DRUG REACTIONS IN HOSPITALIZED PATIENTS AT A TERTIARY CARE HOSPITAL - CD, PARIKH; CK, DESAI; JD, KAPADIA; MK, SHAH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to compare six causality assessment (CA) tools for suspected adverse drug reactions (ADRs) reported in hospitalized patients at a tertiary care hospital in India. Methods: Intensive ADR monitoring was performed in indoor patients of two randomly selected medicine units. A detailed case report of each suspected ADR (n=120) was provided to six independent experts for CA using either visual analog scale (VAS) or WHO-UMC scale. Investigator assessed causality using Naranjo’s scale, Koh et al. scale, the French method, and Karch and Lasagna scale. Similar causality categories from these scales were coded for correlation. Agreement among experts and that between various CA tools were analyzed using Cohen’s kappa and Fleiss kappa. Reasons for disagreements among different scales were evaluated. Results: A variation was observed in the total number of drugs suspected to cause ADR by experts and investigator. “Likely” and “Plausible” causality were suggested frequently by experts using VAS whereas “Possible” causal association was frequent according to experts using the WHO-UMC scale and also by the investigator using algorithms except Koh et al. scale. None to the slight agreement was observed among experts who used VAS (k=0.117), whereas a substantial agreement was observed among experts using the WHO-UMC scale (k=0.707). A substantial agreement was observed between Karch and Lasagna scale and the French method (k=0.740). Both scales demonstrated moderate agreement with Naranjo’s scale. Disagreement among the WHO-UMC scale, the French method, and Karch and Lasagna scale were associated with polypharmacy, serious ADRs, non-availability of laboratory data, and skin and subcutaneous tissue ADRs. Conclusion: A higher inter-rater agreement with the WHO-UMC scale suggests its utility for CA of suspected ADRs in indoor patients. The French method and Karch and Lasagna scale can be used for CA in hospitalized patients as an adjunct to Naranjo’s scale. Factors associated with disagreement should be considered at the time of reporting ADRs and evaluating causality.